Effectiveness of technological options for minimising production risks under variable climatic conditions in eastern Uganda - Kansiime, KM; Shisanya, Chris A.; Wambugu, KS (2014)
This study employed the Just and Pope stochastic production frontier to assess the effectiveness of farmer preferred technologies in reducing production risk related to climate variability in Eastern Uganda. Data for this study were obtained from 315 households, 9 focus group discussions and 23 key informants drawn from Mbale, Pallisa and Sironko districts. Results show that farmers employed a number of technologies/practices strategically in response to seasonal variations in climatic conditions. Most of the technologies showed significant positive impacts on mean yield, but had different risk-reducing effects on yield. Changing sowing dates and crop varieties, soil bunds, compost manure, cover crops, crop rotation and intercropping showed significant (P<0.05) risk-reducing effects on yield. However, their effects varied across agro-ecological zone, except soil bunds and compost manure whose use consistently exhibited both yield-increasing and risk-reducing effects across all the agro-ecologies. Farmer perceptions of technology effectiveness, to some extent, agreed with econometric evidence from this study. Study results have two implications: firstly, the need to develop and disseminate location specific adaptation technologies to reduce production risks, instead of blanket recommendations of similar adaptation measures across locations; and secondly, the need to focus not only on the technical aspects of technologies, but also the social dimensions such as perceptions of smallholder farmers of technology effectiveness, if adoption and retention of adaptation technologies is to be enhanced. Development and research organisations promoting adaptation options should involve farmers in technology evaluation so as to recommend the most feasible options given farmers’ situations and local perceptions.